A Strategic Decision Model Proposal for Open and Distance Flexible Technology-Enabled Learning Environments - Guler, Emel; Karatop, Buket; Kurubacak, Gülsün; Sharma, Ramesh Chander (Voices of Teachers and Teacher Educators, 2021)
Open and distance flexible learning is a strategic issue since it means making the criteria of learning flexible by using technology to support learning. It is necessary to collect data and analyse with analytical methods in order not to succumb to the rapid developments in the environment, especially in technology and to be proactive. In this context, it is necessary to evaluate open and distance flexible learning environments with strategic management principles and to establish continuous development and improvement cycles. This is because the technological changes developing very rapidly in the 21st century we live in reveal the necessity for re-organising open and distance learning environments and the need for continuous improvement. In this study, a model proposal is presented together with a conceptual perspective for a strategy decision model to be developed for open and flexible learning environments. The strategy is the methods and approaches the institution will follow to achieve a goal. Creating strategies in both institutional and educational processes, seeing the progress of the processes, making predictions and planning for the future are important steps to make evaluations. In strategic decision making, attention is drawn to the collection and evaluation of data by analytical methods with a synergistic structure, taking into account the knowledge, experience, wishes and expectations of stakeholders. Within the scope of this study, a research was carried out on how to implement the strategy decision model in developing an open and distance flexible learning environment.